Minocycline Prevents the Development of Mechanical Allodynia in Mouse Models of Vincristine-Induced Peripheral Neuropathy - Starobova, H.; Mueller, A.; Allavena, R.; Lohman, R. J.; Sweet, M. J.; Vetter, I. (Frontiers in Neuroscience, 2019)
Vincristine is an antineoplastic substance that is part of many chemotherapy regimens, used especially for the treatment of a variety of pediatric cancers including leukemias and brain tumors. Unfortunately, up to 90% of vincristine-treated patients develop peripheral neuropathy, a side effect characterized by sensory, motoric and autonomic symptoms. The sensory symptoms include pain, in particular hypersensitivity to light touch, as well as loss of sensory discrimination to detect vibration and touch. The symptoms of vincristine-induced neuropathy are only poorly controlled by currently available analgesics and therefore often necessitate dose reductions or even cessation of treatment. The aim of this study was to identify new therapeutic targets for the treatment of vincristine-induced peripheral neuropathy by combining behavioral experiments, histology and pharmacology after vincristine treatment. We developed and characterized a mouse model of vincristine-induced peripheral neuropathy based on local injections of vincristine. Vincristine caused dose- and time-dependent mechanical hypersensitivity that developed into mechanical hyposensitivity at high doses, and lead to a pronounced, dose-dependent infiltration of immune cells at the site of injection. Importantly, administration of minocycline effectively prevented the development of mechanical hypersensitivity and infiltration of immune cell at the site of injection in our mouse model of vincristine-induced peripheral neuropathy. Similarly, Toll-like receptor 4 knock out mice showed diminished vincristine-induced mechanical hypersensitivity and immune cell infiltration. These results provide evidence for the involvement of Toll-like receptor 4 in the development of vincristine-induced peripheral neuropathy and suggest that minocycline and/or direct Toll-like receptor 4 antagonists may be an effective preventative treatment for patients receiving vincristine.